Elderly care with alzheimer disease: a focus on the theory of cultural care - Ramos, Jose Lúcio Costa; Menezes, Maria do Rosário de (Rev Rene, 2012)
This report was aimed in reflecting on care for the elderly with Alzheimer disease, through family care, focused on Madeleine Leininger’s Theory of Diversity and Universality of Cultural Care. Qualitative study, with 20 home care workers looking after elderly people in Salvador, BA, Brazil, was performed between June and August of 2010.Four categories emerged: characterization of family caregivers of elders with Alzheimer's disease, knowledge about the disease to the practice of caring for the family, the meaning to take proper care provided by family caregivers of seniors with Alzheimer's disease and care for elderly people with Alzheimer's disease. The findings of this study emphasize the importance of the nurse's role as mediator in the relationship between the elderly, family and health team, as well as the relevance of the application of cultural care in the exercise of this mediation. Through cultural care, the prevention is not only empirical or technical but reaches a practice rooted on theoretical and scientific fundaments.